Risk Management, Sustainability and Leadership - Ivascu, Larisa; Ardelean, Ben-Oni; Sarfraz, Muddassar (IntechOpen, 2023)
Sustainability is an approach increasingly being used by more and more organizations in the pursuit of a circular economy. Sustainability cannot be achieved without risk management. As such, this book discusses the risk management process, which is integral to meeting organizational objectives. Chapters address such topics as risk analysis, risk management models, communication and leadership, managing risk in different countries and industries, and much more. The book examines innovative approaches that meet the needs of risk management, sustainability, and leadership.